FAKTOR AFEKTIF DALAM PEMEROLEHAN BAHASA ARAB SEBAGAI BAHASA KEDUA: KAJIAN PUSTAKA TENTANG LANGUAGE ANXIETY - Muhammad Miqdad Abdussalam; Nurhalim; Vivi Dwi Clarisa; Zaenal Rafli; Erlina (Universitas Islam Negeri Palopo, 2026)
This study examines the role of affective factors, particularly language anxiety, in the acquisition of Arabic as a second language. The background of this research is based on the fact that successful language learning is not only influenced by cognitive factors, but also by emotional variables such as motivation, self-confidence, and anxiety, as explained in Krashen’s Affective Filter Hypothesis. The aim of this study is to explore the concept, causes, impacts, and strategies for addressing language anxiety in Arabic language learning. This research employs a library research method with a descriptive qualitative approach. Data were collected from various relevant sources, including journal articles, books, and previous studies, and analyzed using content analysis techniques. The findings indicate that language anxiety is influenced by internal factors such as low self-confidence, lack of learning motivation, and limited vocabulary mastery, as well as external factors such as the learning environment and teaching methods. Language anxiety has a negative impact on learners’ concentration, working memory, participation, and overall achievement in Arabic language skills. Therefore, supportive and communicative teaching strategies, along with the teacher’s role as a facilitator, are essential to minimize anxiety and enhance the success of Arabic language acquisition. abstrak Penelitian ini membahas peran faktor afektif, khususnya language anxiety (kecemasan berbahasa), dalam pemerolehan bahasa Arab sebagai bahasa kedua. Latar belakang penelitian ini didasarkan pada kenyataan bahwa keberhasilan pembelajaran bahasa tidak hanya dipengaruhi oleh faktor kognitif, tetapi juga oleh faktor emosional seperti motivasi, kepercayaan diri, dan kecemasan sebagaimana dijelaskan dalam Affective Filter Hypothesis oleh Stephen Krashen. Tujuan penelitian ini adalah untuk mengkaji konsep, faktor penyebab, dampak, serta strategi penanganan kecemasan berbahasa dalam pembelajaran bahasa Arab. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan pendekatan kualitatif deskriptif. Data diperoleh dari berbagai sumber literatur seperti artikel jurnal, buku, dan penelitian terdahulu yang relevan, kemudian dianalisis menggunakan teknik analisis isi (content analysis). Hasil penelitian menunjukkan bahwa kecemasan berbahasa dipengaruhi oleh faktor internal seperti rendahnya kepercayaan diri, motivasi belajar, dan penguasaan kosakata, serta faktor eksternal seperti lingkungan belajar dan metode pembelajaran. Kecemasan berbahasa berdampak negatif terhadap konsentrasi, working memory, partisipasi, dan pencapaian keterampilan berbahasa Arab. Oleh karena itu, strategi pembelajaran yang suportif, komunikatif, serta peran guru sebagai fasilitator sangat diperlukan untuk meminimalkan kecemasan dan meningkatkan keberhasilan pemerolehan bahasa Arab.